Strategi Kampanye Partai Golkar Pada Pemilihan Umum 2024 Di Kota Serang - Sudrajat, Rizky (Universitas Sultan Ageng Tirtayasa, 2024)
This research aims to analyze the strategy implemented by the Golkar Party in gaining public support in Serang City ahead of the 2024 Election. The main focus of this research is on efforts to increase voter support in order to win the election. With a qualitative approach, data was collected through interviews, observation and documentation involving the Chair of the DPD, the Election Winning Body, political observers and the local community. Research findings show that the Golkar Party's campaign strategy includes identifying potential voters, strengthening volunteer networks, and using social media to reach voters. The conclusion of this research emphasizes that the synergy between digital strategy, conventional campaigns and flexible communication makes a major contribution to the effectiveness of the Golkar Party's campaign.